2015
DOI: 10.1080/23251042.2015.1046584
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption and working hours: a longitudinal study of developed and developing nations, 1990–2008

Abstract: This study advances sociological research on the environmental impacts of working hours. Proponents of economic degrowth propose that a reduction in working time slows economic growth, which yields both social and environmental benefits. Building on such arguments, the authors conduct longitudinal analyses of the effects of average annual working hours on total energy consumption for samples of both developed and developing nations, and assess the extent to which the effect of working hours on energy consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…The third theoretical approach suggests that growth in domestic income inequality may increase carbon emissions by increasing status‐based consumption (Schor 1996), prolonging working hours (Bowles and Park , Fitzgerald et al. , Knight et al. ), and impeding diffusion of green innovations to the mass market (Vona and Patriarca ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third theoretical approach suggests that growth in domestic income inequality may increase carbon emissions by increasing status‐based consumption (Schor 1996), prolonging working hours (Bowles and Park , Fitzgerald et al. , Knight et al. ), and impeding diffusion of green innovations to the mass market (Vona and Patriarca ).…”
Section: Resultsmentioning
confidence: 99%
“…From this perspective, rising income inequality can increase status‐based consumption as individuals spend more and more to emulate the standards set by the wealthier members of society in what we may call a Veblenian effect (Schor ; Veblen ). Average working hours have also been shown to increase with rising income inequality (Bowles and Park ), and recent cross‐national research indicates that longer working hours are associated with greater environmental impacts (Fitzgerald, Jorgenson, and Clark ; Knight, Rosa, and Schor ). A final mechanism concerns the diffusion of innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another approach argues that rising income inequality can increase statusbased consumption of goods and fossil fuels as individuals spend more and more to emulate the standards set by the "overconsuming" wealthier members of society in what we may call a Veblen effect (Schor, 1998;Veblen, 1934). Average working hours have also been shown to increase with rising income inequality (Bowles & Park, 2005), and recent cross-national research indicates that longer working hours are associated with greater environmental impacts, including growth in energy consumption and carbon emissions (Fitzgerald, Jorgenson, & Clark, 2015;Knight, Rosa, & Schor, 2013). Vona and Patriarca (2011) find that in wealthy countries, growth in income inequality reduces the development and diffusion of environmentally beneficial consumer products because it creates a larger gap between what wealthy early adopters are willing to pay and what the less wealthy can afford.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The first, which is known as the Veblen Effect, is that inequality induces status consumption as households increase their spending to keep up with the visible lifestyles of higher-income households (Veblen 1934;Schor 1998). Second, income inequality has been shown to have a positive association with the level of working hours (Bowles and Park 2005), and recent studies have shown that increased working hours are drivers of energy consumption and CO 2 emissions via both their impacts on economic development and on the consumption choices of households (Fitzgerald et al 2015;Knight, Rosa, and Schor 2013).…”
Section: Brief Literature Reviewmentioning
confidence: 99%